03. Dada a função f(x) = 2x – 1, determine:
a) f(2)
b) f(-1)
c) f(1)
d) f(0)
e) f(22)
Soluções para a tarefa
Respondido por
2
Substitua o valor de x na fórmula:
a) f(2) = 2(2) - 1
a) f(2) = 3
b) f(-1) = 2(-1) - 1
b) f(-1) = -3
c) f(1) = 2(1) - 1
c) f(1) = 1
d) f(0) = 2(0) - 1
d) f(0) = -1
e) f(22) = 2(22) - 1
e) f(22) = 43
a) f(2) = 2(2) - 1
a) f(2) = 3
b) f(-1) = 2(-1) - 1
b) f(-1) = -3
c) f(1) = 2(1) - 1
c) f(1) = 1
d) f(0) = 2(0) - 1
d) f(0) = -1
e) f(22) = 2(22) - 1
e) f(22) = 43
Perguntas interessantes
Biologia,
8 meses atrás
Inglês,
8 meses atrás
Biologia,
10 meses atrás
Informática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás